A Systematic Exfoliation of Prior Arts About The Use of Natural and Synthesized 1,4-Naphthoquinones Towards Corrosion Inhibition - Saralaya, Sanjay Sukumar; Kanakamajalu, Shridhara (Walisongo Journal of Chemistry, 2024)
In this review segment, use of natural and synthesized 1,4-naphthoquinones for corrosion inhibition was comprehensively covered based on the past research disclosures. The prior arts were gathered from various research article repositories by the use of search terms like ‘Quinonoids as corrosion inhibitors’ and ‘1,4-Napthoquinones as corrosion inhibitors’ as a part of direct referencing. Additionally, back and cross referencing were also done to ensure the complete collection of prior arts. This work will help the researchers to understand the credibility of 1,4-naphthoquinones as corrosion inhibitors in the global platform. Interestingly, the henna leaf extract (aqueous or solvent mediated) having 2-hydroxy 1,4-naphthoquinone (Lawsone, NQ-12) was the most explored phytochemical under natural or green corrosion inhibitor category. More importantly, a few natural extracts having 1,4-naphthoquinones were widely used as corrosion inhibitors in different mediums. With regard to phytochemical extracts, the collective inhibition ability of many phytochemicals will add to corrosion inhibition process. But in recent years, we can observe the use of specific compounds (synthesized/isolated derivatives of 1,4-naphthoquinone) as alone for the intended corrosion inhibition. Under the context of immediate scope, we have disclosed around 23-26 new molecules having 1,4-naphthoquinone framework for experimental ventures towards corrosion inhibition. This work would favor the use of some new 1,4-naphthoquinones in its pure form towards  retarding corrosion with the assistance of  supportive molecular framework.